2009
DOI: 10.1111/j.1468-2958.2009.01344.x
|View full text |Cite
|
Sign up to set email alerts
|

Self-Report and Psychophysiological Responses to Fear Appeals

Abstract: This study was designed to assess the relationship between self-report and psychophysiological responses to fear appeals and behavioral changes elicited by these. Ninety-two subjects watched one of four messages that varied in level of threat (high vs. low) and efficacy (high vs. low). Concomitantly, psychophysiological measures (heart rate and skin conductance) were registered. Perceived threat and efficacy varied according to the characteristics of the message. High-threat messages elicited significantly dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 36 publications
5
34
0
1
Order By: Relevance
“…Further, self-reported ratings of subjective arousal were consistent with the objective SCR findings (i.e., higher arousal self-ratings which corresponded with the detected increases in SCR activity). Similarly, Ordoñana et al (2009) found that participants rated greater fear and showed increased SCR activity towards high threat-based tetanus vaccination messages compared with the low threat-based message. Collectively, these studies reveal consensus between the self-report and objective measures of arousal and highlight that advertisements that contain emotional stimuli may generate greater automatic arousal responses.…”
Section: Psychophysiological Measures Of Persuasive Processingmentioning
confidence: 82%
See 1 more Smart Citation
“…Further, self-reported ratings of subjective arousal were consistent with the objective SCR findings (i.e., higher arousal self-ratings which corresponded with the detected increases in SCR activity). Similarly, Ordoñana et al (2009) found that participants rated greater fear and showed increased SCR activity towards high threat-based tetanus vaccination messages compared with the low threat-based message. Collectively, these studies reveal consensus between the self-report and objective measures of arousal and highlight that advertisements that contain emotional stimuli may generate greater automatic arousal responses.…”
Section: Psychophysiological Measures Of Persuasive Processingmentioning
confidence: 82%
“…Although such psychophysiological measures are relatively uncommon in research within the road safety advertising context, in the health communication context more broadly, a number of studies have applied SCR to assess psychophysiological responses and, in doing so, have highlighted the value of using such objective measures to assess automatic arousal (e.g., Lee and Lang 2009;Ordoñana et al 2009;Strasser et al 2009;Xu 2014). Lee and Lang (2009), for instance, examined SCRs to the emotional content of fear, anger, joy, and sadness, while participants were viewing a range of television messages.…”
Section: Psychophysiological Measures Of Persuasive Processingmentioning
confidence: 99%
“…When fear is measured in an empirical study, it is usually assessed by participants indicating how "frightened," "scared," and "anxious" they are about a specific health threat (e.g., McMahan et al, 1998). At least one study assessed fear through physiological measurements-changes in skin conductance and heart rate (Ordoñana, González-Javier, Espín-López, & Gómez-Amor, 2009). However, a fear-arousing message could produce diverse physiological reactions such as fight, flight, freezing, or simply increased attention depending on the situational and individual differences (Bradley & Lang, 2007).…”
Section: Fearmentioning
confidence: 99%
“…Future research should look into measuring fear on a continuous basis, either through dial (by continuously turning a dial during the exposure to indicate their feelings of fear) or physiological measurements (e.g., Ordoñana et al, 2009).…”
Section: Proposition 4 As Perceived Threat Increases When Perceived mentioning
confidence: 99%
See 1 more Smart Citation